2004
DOI: 10.1093/ije/dyh074
|View full text |Cite
|
Sign up to set email alerts
|

Weight-for-age malnutrition in Indonesian children, 1992-1999

Abstract: Disparities among social and economic groups have narrowed over time in Indonesia; the relatively high risk of male children compared with females has also decreased. Maternal education and economic status-as measured by quintile of adjusted per-capita household expenditures-have continued to be very strong predictors of children's nutritional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 12 publications
7
25
0
Order By: Relevance
“…Incidence of under-five mortality declined sharply as mother"s level of education increases. The result buttresses the studies of Waters et al (2004) and Boyle et al (2006) that mother"s education is positively associated with a number of measures of infant and child health and nut ritional status. Also, the above finding may be explained by Isiugo-A banihe"s (2003) in observation that education has been identified as affecting all as pects of people"s lives and it is intricately linked with t he demographic process.…”
Section: Discussion Of Findingssupporting
confidence: 56%
See 1 more Smart Citation
“…Incidence of under-five mortality declined sharply as mother"s level of education increases. The result buttresses the studies of Waters et al (2004) and Boyle et al (2006) that mother"s education is positively associated with a number of measures of infant and child health and nut ritional status. Also, the above finding may be explained by Isiugo-A banihe"s (2003) in observation that education has been identified as affecting all as pects of people"s lives and it is intricately linked with t he demographic process.…”
Section: Discussion Of Findingssupporting
confidence: 56%
“…Hossain et al (2002) supported a direct causal relationship between mother"s education and child mortality. Waters et al (2004) observed that mother"s education is positively associated with a number of measures of infant and child health and nutritional status. Mothers" plac e of residence (urbanrural distinction) has been used in some developing countries as a proxy measure for li ving conditions to illustrate bot h public and medical health provisions (Suwal, 2001).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…In Cameroon, for instance, Pongou et al (2006b) showed that the economic crises and large economic adjustment in the 1990s had a long-term impact on child health and survival. Waters et al (2004) found in Indonesia that, maternal education and economic status-as measured by quintile of adjusted per-capita household expenditures-were very strong predictors of children's nutritional outcomes. In most African countries, under worsening socio-economic conditions, there is a decreased attendance at routine health checks which in turn affects children nutritional status (Prevel et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies confirmed that economic conditions influ ence the quality and quantity of consumed foods and consequently can be a key factor in the nutritional sta tus of people (12)(13)(14). In addition, in the case of chil dren, the level of their parent education is an important factor which can alter their nutritional status and growth (15)(16)(17). However, these relationships have not been confirmed in Nepal.…”
mentioning
confidence: 99%